2018
DOI: 10.1002/jcb.26575
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of HSP27 in atherosclerosis and coronary heart disease by inhibiting reactive oxygen species

Abstract: HSP27 exerts its protective role by suppressing ROS and AS progression by inhibiting mitochondria apoptosis pathway in CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Contrary to these results, circulating HSP27 levels were reported as decreased >70% in patients with carotid stenosis [8] and coronary artery diseases (CAD) compared with healthy subjects [25]. In addition to reduced concentrations of HSP27, patients with CAD in these two studies had more severe comorbidities compared to patients with higher HSP27 level in Park's and Zhang HL's studies [23,24], including diabetes and hypertension in both studies and smoking in the former plus hyperlipemia in the latter. Patients in these two studies had serum HSP27 levels even decreased to a mean value of 0.19 ng/mL and 1.23 ng/mL, respectively.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Contrary to these results, circulating HSP27 levels were reported as decreased >70% in patients with carotid stenosis [8] and coronary artery diseases (CAD) compared with healthy subjects [25]. In addition to reduced concentrations of HSP27, patients with CAD in these two studies had more severe comorbidities compared to patients with higher HSP27 level in Park's and Zhang HL's studies [23,24], including diabetes and hypertension in both studies and smoking in the former plus hyperlipemia in the latter. Patients in these two studies had serum HSP27 levels even decreased to a mean value of 0.19 ng/mL and 1.23 ng/mL, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, Park et al reported that circulating HSP27 levels in acute coronary syndrome (ACS) patients were remarkably higher than those in an age-and sex-matched healthy control group [23]. Compared with controls, a significant increase in serum HSP27 in patients with CHD was also observed in a recent study [24].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Contrary to these results, circulating HSP27 levels were reported as decreased >70% in patients with carotid stenosis [8] and coronary artery diseases (CAD) compared with healthy subjects [25]. In addition to reduced concentrations of HSP27, patients with CAD in these two studies had more severe comorbidities compared with patients having higher HSP27 levels in the studies of Park et al and Zhang et al [23,24], including diabetes and hypertension in both studies and smoking in the former plus hyperlipemia in the latter. Patients in these two studies even had serum HSP27 levels decreased to mean values of 0.19 ng/mL and 1.23 ng/mL, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, Park et al reported that circulating HSP27 levels in acute coronary syndrome (ACS) patients were remarkably higher than those in an age-and sex-matched healthy controls [23]. Compared with controls, a significant increase in serum HSP27 in patients with CHD was also observed in a recent study [24].…”
Section: Discussionmentioning
confidence: 79%